Narrative and Simultaneity: Benjamin's Image of Proust - Louis Simon (Studies in 20th & 21st Century Literature, 1997)
We can better understand Proust's approach to literary activity in A la recherche du temps perdu and Walter Benjamin's reading of the novel in his essay "The Image of Proust" by recognizing how the experience and concept of simultaneity, as opposed to linearity or narrative progression, underlies these texts. Though Proust's novel represents a linear narrative, the writer's activity, which Benjamin characterizes as "the attempt to charge an entire lifetime with the utmost awareness," engages a supralinear dimension of lived experience that binds literary activity to the present moment. Readings of the Benjamin-Proust relationship that focus on an exclusively linear understanding of Proust restrict the possibility of viewing both authors as actively concerned with the impact of literary experience on the present moment. A reading of this relationship that foregrounds the notion of simultaneity, however, allows for a richer appreciation of affinities between the two writers and their attitudes toward experience, action, and consciousness.
Keywords: Walter Benjamin; Proust; A la recherche du temps perdu; The Image of Proust; linearity; narrative progression; linear narrative; writer' s activity; supralinear dimension; supralinear; lived experience; literary activity; present; moment; restrict; impact; experience; present moment; relationship; simultaneity; time; action; consciousness